Multi-version approach to improve the reliability of processing data of the earth remote sensing in the real-time - Saramud Mikhail V.; Kovalev Igor V.; Losev Vasiliy V.; Petrosyan Mariam O.; Kovalev Dmitriy I. (E3S Web of Conferences, 2019)
The article describes the use of a multi-version approach to improve the accuracy of the classification of images when solving the problem of image analysis for Earth remote sensing. The implementation of this approach makes it possible to reduce the classification error and, consequently, to increase the reliability of processing remote sensing data. A practical study was carried out in a multi-version real-time execution environment, which makes it possible to organize image processing on board of an unmanned vehicle. The results confirm the effectiveness of the proposed approach.